3D printed objects do not impact the behavior of a coral-associated damselfish or survival of a settling stony coral - Ruhl, Emily J.; Dixson, Danielle L. (PLOS ONE, 2019)
3D printing technology offers significant advantages in the development of objects and tools across an array of fields and has been implemented in an increasing number of ecological studies. As rates of degradation or chemical leaching of 3D printed models has not been well documented under environmental conditions, it is essential to examine if these objects will alter the behavior or impact the survivorship of the focal species prior to widespread implementation. Here, we explored the efficacy of using 3D printed models in coral reef behavioral research, an area of study where this form of additive manufacturing could offer significant advantages. Coral-associated blue-green chromis (Chromis viridis) individuals were exposed to natural and 3D printed coral habitats, and larval mustard hill coral (Porites astreoides) were offered 3D printed substrate as a settlement surface. Habitat association and behavioral analyses indicated that C. viridis did not discriminate or display modified behaviors between 3D printed and natural coral skeletons or between 3D printed materials. P. astreoides displayed significantly higher settlement when provided with 3D printed settlement surfaces than when provided with no settlement surface and settled at similar rates between 3D printed surfaces of differing materials. Additionally, growth and mortality of P. astreoides settled on different 3D printed surfaces did not significantly differ. Our results suggest that the 3D printed models used in this study are not inherently harmful to a coral reef fish or species of brooding coral, supporting further exploration of the benefits that these objects and others produced with additive manufacturing may offer as ecological research tools.